Securing the Digital Future: A Proactive Legal Framework for Quantum Computing Challenges - Ghazaleh, Shereen Abu; Alabady, Hassan Sami; Al-Khaldi, Inas; Abu-Moghli, Mohannad Azmi Masod (Journal of Cultural Analysis and Social Change, 2025)
Quantum computing is transitioning rapidly from theoretical possibility to practical capability, generating unprecedented legal and regulatory challenges across intellectual property, cybersecurity, data protection, and contractual liability. Despite early governmental initiatives, including the European Union’s Quantum Flagship, the U.S. National Quantum Initiative Act, and the G7’s 2025 Kananaskis Common Vision, existing governance efforts remain fragmented, programmatic, and insufficiently attuned to the systemic risks posed by quantum technologies. This article employs a doctrinal, comparative, and policy-analytic methodology to evaluate the preparedness of current legal frameworks and to identify the structural gaps that emerge when quantum capabilities threaten cryptographic stability, undermine data-protection assumptions, and strain patent doctrines. The findings show that quantum risks are foreseeable, cross-domain, and capable of rendering existing compliance mechanisms ineffective. The study’s novel contribution lies in synthesizing these insights into an integrated governance model that mandates quantum-resistant cryptography, modernizes intellectual property standards, recalibrates data-protection obligations, and incorporates quantum-specific contingencies into contractual risk management. The article argues that only a proactive, harmonized, and anticipatory regulatory architecture can ensure that quantum technologies develop in accordance with the rule of law, global security, and the public interest.